Granulocyte colony-stimulating factor- and chemotherapy-induced large-vessel vasculitis: six patient cases and a systematic literature review - Kirsi Taimen; Samu Heino; Ia Kohonen; Heikki Relas; Riikka Huovinen; Arno Hänninen; Laura Pirilä (Oxford University Press, 2022)
Patients receiving chemotherapy are prone to neutropoenic infections, presenting with non-specific symptoms such as a high fever and elevated inflammatory parameters. Large-vessel vasculitis (LVV) may have a similar clinical presentation and should be included in differential diagnostics. A few published case reports and adverse event reports suggest a causal association between LVV and the use of granulocyte colony-stimulating factor (G-CSF) and chemotherapy. Our objective was to evaluate the relationship between LVV, G-CSF and chemotherapy.
Methods
Between 2016 and 2018, we identified six patients in Finland with probable drug-induced LVV associated with G-CSF and chemotherapy. All six patients had breast cancer. A systematic literature review was performed according to PRISMA guidelines using comprehensive search terms for cancer, chemotherapy, G-CSF and LVV.
Results
The literature search identified 18 similar published case reports, of which most were published after 2014. In all patients combined (n = 24), the time delay from the last drug administration to the LVV symptoms was on average 5 days with G-CSF (range = 1–8 days) and 9 days with chemotherapy (range = 1–21 days). Common symptoms were fever (88%), neck pain (50%) and chest pain (42%). Based on imaging, 17/24 (71%) had vascular inflammation in the thoracic aorta and supra-aortic vessels, but 5/24 (21%) reportedly had inflammation limited to the carotid area.
Conclusion
This review suggests that LVV may be a possible serious adverse event associated with G-CSF and chemotherapy. Successful management of drug-induced LVV requires early identification, through diagnostic imaging, and discontinuation of the drug.